Unique characteristics of the J-domain proximal regions of Hsp70 cochaperone Apj1 in prion propagation/elimination and its overlap with Sis1 function - Ganser, Samantha J.; McNish, Bridget A.; Schwanitz, Gillian L.; Delaney, John L.; Corpus, Bridget A.; Schilke, Brenda A.; Biswal, Anup K.; Sahi, Chandan; Craig, Elizabeth A.; Hines, Justin K. (Frontiers in Molecular Biosciences, 2024)
J-domain proteins (JDPs) are obligate cochaperones of Hsp70s. The Class A JDP Apj1 of the yeast cytosol has an unusually complex region between the N-terminal J-domain and the substrate binding region-often called the Grich or GF region in Class A and B JDPs because of its typical abundance of glycine. The N-terminal 161-residue Apj1 fragment is known to be sufficient for Apj1 function in prion curing driven by overexpression of Hsp104. Further analyzing the N-terminal segment of Apj1, we found that a 90-residue fragment that includes the 70-residue J-domain and the adjacent 12residue glutamine/alanine (Q/A) segment is sufficient for curing. Furthermore, the 121-residue fragment that includes the Grich region was sufficient not only to sustain the growth of cells lacking the essential Class B JDP Sis1, but also enabled the maintenance of several prions normally dependent on Sis1 for propagation. A J-domain from another cytosolic JDP could substitute for the Sis1-related functions, but not for Apj1 in prion curing. Together, these results separate the functions of JDPs in prion biology and underscore the diverse functionality of multi-domain cytosolic JDPs in yeast.